Penerapan Proteksi Radiasi di Desa Kangkung Kabupaten Kendal - Andriani, Intan; Tsania, Novia Putri (Universitas Pahlawan Tuanku Tambusai, 2024)
In the use of radiation, attention must be paid to radiation safety. Radiation safety is carried out to protect workers, community members, and the environment from radiation hazards (BAPETEN, 2013). Knowledge about radiation protection when conducting radiological examinations is still very low known by the people of Kangkung village, Kendal regency. For this reason, it is necessary to educate the community so that the occurrence of biological effects can be minimized. The PkM team will provide counseling related to the application of radiation protection that needs to be known and carried out while in the X-ray radiation source area. The method that will be carried out by the PkM team is to provide pre-test, counseling and post test. The results of the implementation of community service activities show that residents have understood the counseling material provided. This is shown by the increase in knowledge after counseling on radiation hazards, radiation protection and the application of personal protective equipment for radiological examinations. According to Manurung (2018), the better the knowledge that individuals have, the better the perception of the dangers of x-ray radiation.